Making Sense: Harnessing Communication through Prototyping. (28th July 2017) - Innella, Giovanni; Rodgers, Paul A.
Abstract: This paper reports on the experiences gathered from an international collaborative workshop where participants were invited to continuously build and prototype their ideas, rather than following conventional stages such as idea generation, visualization and, only later, prototyping. Adopting a hands-on approach proved beneficial in the communication among participants as well as simplifying the design process. By developing quick and approximate prototypes, participants more easily expressed their ideas whilst overcoming language barriers. Furthermore, the prototypes helped participants to identify the key aspects of their proposals and focus on those. Finally, the prototypes also served as useful props to enact the experience of using the proposed artefacts and services. The findings of the workshop highlight that when working with mixed groups of participants with diverse skills, different cultural backgrounds and languages, a hands-on approach can be extremely useful. Prototyping in design workshops here proved valid on both the communication and the creative processes.